Modern educational technologies within the pedagogical training program for newly employed university professors (analytical reading) - bounif, mohamed amine; lamine, nasira (Journal of Social Sciences and Humanities, 2024)
This study comes to shed light on the contents of modern educational technologies directed at the formation of newly employed university professors in order to enable him to possess the various technical skills required to achieve quality education. We concluded, through the results of the study, that including these contents contributes to upgrading the supervision of the university professor and developing the methods of transferring knowledge to his students, as well as Pedagogical accompaniment through the national platform for distance pedagogical training for the benefit of university professors contributes to improving their academic performance, the outcomes of which will reflect positively on the quality of university education